Współpraca przedsiębiorstw energetycznych i gmin w świetle art. 16 ust. 12 ustawy Prawo energetyczne - Tatarkiewicz, Piotr (Wydawnictwo Uniwersytetu Wrocławskiego, 2014)
The study presents the analysis and evaluation of mutual relations between communes planning network infrastructure on their territories, as seen from the perspective of cooperation duty enacted in Article 16, paragraph 12 of the Act of 10 April 1997 Journal of Laws item 1059 with further amendments. Planning of supply of electricity and gas is, in accordance with Article 7, paragraph 1 of the Act on Commune self-government of 8 March 1990 Journal of Laws item 594 with further amendments, one of the commune’s own tasks. However, commune’s energetics would not be able to function without the participation of energy companies. An important element of cooperation of communes and energy companies in commune energetics is a cooperation of entities, which concerns planning of network infrastructure on commune territories, since the commune and energy company make plans in the same area. Article 16, paragraph 12 of Energy law does not enact, however, any rules or mechanisms of such cooperation. It merely shows the aims of cooperation, such as rationality of investment, which can be achieved by ensuring cohesion of the commune and energy company plans. This rationality can be difficult to achieve because of divergent goals, responsibilities and tasks which bind, while planning, both communes and energy companies. The civil law instrument, which in case of any divergence between plans can protect the communal plan, is the agreement based on Article 20, paragraph 5 of Energy law.
Keywords: prawo energetyczne; przedsiębiorstwa energetyczne; gminy wyznaniowe; współpraca